THE USE OF ONLINE AND OFFLINE PROCESSING TOOLS TO IMPROVE THE PRECISION OF A GPS PASSIVE STATION - ADAM, SARHAT MUSTAFA (Journal of Duhok University, 2017)
Founding of local geodetic points is very crucial for many purposes such as surveying and mapping. In 2011, a control marker was established at the engineering college, University of Duhok (UoD). A survey campaign was carried out to collect GPS raw data of roughly 121 h using Leica Viva GNSS tool at 1-second epoch. The aim was to install an accurate and dependable geodetic point which usually known as the passive station. The accuracy of the established point cannot be reliably checked or compared due to unavailability of any reliable and precise geodetic point near the survey marker. In this paper, investigating the accuracy of that recognized position using the statistical testing is aimed. For that reason, 121 h of raw data was broken into 36 sub-files covering five days of observations, each containing a full of 24 h, 12 h and 6 h of data at 1-second epoch. The data was separately processed utilizing different processing solutions such as free available online PPP services and post processing desktop tool. The aim is to compare the position of each of the subsamples with the most probable value. The results showed that the last recognized and dependable point coordinates are 314075.7788, 4080892.2610, and 525.1899 (m) with RMSE ±3.7, ±3.9, ±6.2 (mm), respectively.